Towards enterprise architecture frameworks for complex evolving systems and organisations. (12th July 2011) - Zacarias, Marielba; Reis, Paulo; Pinto, H. Sofia
Enterprise modelling frameworks are effective tools to communicate organisation's structure, processes, and information systems. However, an increasingly interconnected, dynamic, and uncertain world is pressing to regard organisations and information systems as complex evolving systems. This paper: 1) argues the importance of using complexity principles in analysing, modelling and (re)designing organisations and its information systems; 2) discusses the conceptual implications and limitations of current enterprise modelling frameworks regarding complexity principles; 3) proposes an extension to overcome such limitations; 4) illustrates some benefits of this extension with a case study.